New language resources, tools and services for morphological processing - Tadić, Marko (2013)
In the presentation newly available language resources, tools and services for morphological processing of ca 30 European languages are presented. These resources are accessible through LT sharing platform META-SHARE that was build within the META- NET NoE, and particularly within its sub-part project CESAR.
Projekt MZOS
ENG